1995
DOI: 10.1080/09553009514551551
|View full text |Cite
|
Sign up to set email alerts
|

Induction of DNA Single-strand Breaks in Human Lymphocytes by Low Doses of γ-rays

Abstract: We hypothesized that very low doses of gamma-rays have a genotoxic effect as measured by DNA single-strand breaks (ssbs). To test our hypothesis we used a newly developed alkaline microgel electrophoretic technique to quantitate DNA ssbs in freshly isolated human lymphocytes. An enhanced sensitivity to detect low levels of DNA damage was made possible by this method due to an additional step of DNA precipitation by ethanol in agarose microgels. We exposed lymphocytes from three subjects for 1 h at 4 degrees C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
3

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(23 citation statements)
references
References 33 publications
0
20
0
3
Order By: Relevance
“…In both cell lines, treatment with 20 mg/ml MMS for 2 and 24 h induced increases in all three comet parameters (Olive tail moment, tail DNA, and tail length), although the survival of the cells did not differ from the background after either 2 or 24 h of treatment (A172: 2 h, 91.0% vs. 96.0%; 24 h, 91.0% vs. 98.8%; IMR-90: 2 h, 93.7% vs. 96.3%; 24 h, 90.6% vs. 95.9%). Figure 2 shows the DNA strand breaks in A172 and IMR-90 cells after culture with different concentrations of MMS for 2 or 24 h. In our comet assay protocol, the cell suspensions and low melting point agarose layered onto slides were treated with 1 mg/ml proteinase K to increase the sensitivity, since Singh et al [1995] reported that proteinase K treatment of cells allowed the detection of DNA strand breaks in human lymphocytes irradiated with low doses of g rays. Our results further confirmed that proteinase K treatment of the cells raised the sensitivity of detection of DNA strand breaks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In both cell lines, treatment with 20 mg/ml MMS for 2 and 24 h induced increases in all three comet parameters (Olive tail moment, tail DNA, and tail length), although the survival of the cells did not differ from the background after either 2 or 24 h of treatment (A172: 2 h, 91.0% vs. 96.0%; 24 h, 91.0% vs. 98.8%; IMR-90: 2 h, 93.7% vs. 96.3%; 24 h, 90.6% vs. 95.9%). Figure 2 shows the DNA strand breaks in A172 and IMR-90 cells after culture with different concentrations of MMS for 2 or 24 h. In our comet assay protocol, the cell suspensions and low melting point agarose layered onto slides were treated with 1 mg/ml proteinase K to increase the sensitivity, since Singh et al [1995] reported that proteinase K treatment of cells allowed the detection of DNA strand breaks in human lymphocytes irradiated with low doses of g rays. Our results further confirmed that proteinase K treatment of the cells raised the sensitivity of detection of DNA strand breaks.…”
Section: Discussionmentioning
confidence: 99%
“…After the exposure, the RF field, sham and 20 mg/ml MMS samples were processed for the alkaline comet assay as described by Singh et al [1994Singh et al [ , 1995. Briefly, the cells were washed, resuspended in Ca 2þ -and Mg 2þ -free phosphate buffered saline at a concentration of 1 Â 10 5 cells/ml, and mixed with 1% low melting point agarose at a ratio of 1:5.…”
Section: Alkaline Comet Assaymentioning
confidence: 99%
“…This method is more sensitive than other available methods in detecting DNA strand breaks. It can detect DNA single-strand breaks induced by 0.01 Gy of γ-rays (Singh et al 1995) or 0.032 Gy of X rays (Singh et al 1994), and double-strand breaks induced by 0.125 Gy of X rays (Singh and Stephens 1997) in human lymphocytes.…”
Section: Methodsmentioning
confidence: 99%
“…Gamma rays directly induced the CA in human lymphocytes (Brandriff et al 1988, Lefrancois et al 1989, Lijima and Morimoto 1991, Milkovic-Kraus et al 1992, Huber et al 1992, Kosaka et al . 1995, Sing et al 1995, Kasai et al 1996, Chambrette et al 1996, Garcia-Sagredo et al 1996, in human chorionic villi (Salvi et al 1993), in Macaca mulatta lymphocytes (Guedeney et al 1988), in cynomolgus peripheral lymphocytes (Guedeney et al 1989), in rhesus monkey (Van Buul 1989) and in mouse (Sjoblom et al 1995, Zang 1995. It is shown that gamma rays directly and indicrectly affected the DNA and caused to chromosome mutation.…”
Section: Discussionmentioning
confidence: 99%